Lipopolysaccharide Induces Mitochondrial Fragmentation and Energetic Shift in Reactive Microglia: Evidence for a Cell-Autonomous Program of Metabolic Plasticity - Marcelle Pereira dos Santos; Vitor Emanuel Leocadio; Lívia de Sá Hayashide; Mariana Marques; Clara Fernandes Carvalho; Antonio Galina; Luan Pereira Diniz (Toxins)
Microglia, the resident immune cells of the central nervous system (CNS), play essential roles in maintaining brain homeostasis. While transient activation is protective, chronic microglial reactivity contributes to neuroinflammatory damage and neurodegeneration. The mitochondrial mechanisms underlying this shift remain poorly understood. Here, we investigated whether lipopolysaccharide (LPS) induces coordinated mitochondrial and metabolic alterations in BV-2 microglial cells. LPS stimulation (100 ng/mL, 24 h) induced a reactive phenotype, with increased Iba1 (+82%), F4/80 (+132%), and Cd68 (+44%), alongside elevated hydrogen peroxide (~6-fold) and nitrite (~45-fold). Cytotoxicity increased by 40% (LDH assay), and cell viability dropped to ~80% of the control (MTT). Extracellular lactate increased, indicating glycolytic reprogramming. However, LPS-primed cells showed greater ATP depletion under antimycin A challenge, reflecting impaired metabolic flexibility. Hoechst staining revealed a ~4-fold increase in pyknotic nuclei, indicating apoptosis. Mitochondrial dysfunction was confirmed by a 30–40% reduction in membrane potential (TMRE, JC-1), a ~30% loss of Tomm20, and changes in dynamics: phospho-Drp1 increased (+23%), while Mfn1/2 decreased (33%). Despite a ~70% rise in Lamp2 signal, Tomm20–Lamp2 colocalization decreased, suggesting impaired mitophagy. High-resolution respirometry revealed decreased basal (−22%), ATP-linked (24%), and spare respiratory capacity (41%), with increased non-mitochondrial oxygen consumption. These findings demonstrate that LPS induces mitochondrial dysfunction, loss of metabolic adaptability, and increased apoptotic susceptibility in microglia. Mitochondrial quality control and energy flexibility emerge as relevant targets to better understand and potentially modulate microglial responses in neuroinflammatory and neurodegenerative conditions.